Influence of starter culture and a protease on the generation of ACE-inhibitory and antioxidant bioactive nitrogen compounds in Iberian dry-fermented sausage “salchichón” - Fernández, Margarita (Heliyon, 2016)
The effect of the addition of an autochthonous starter culture and the protease EPg222 on the generation of angiotensin-I–converting enzyme (ACE)-inhibitory and antioxidant compounds by the dry-fermented sausage “salchichón” was investigated. Sausages were prepared with purified EPg222 and Pediococcus acidilactici MS200 and Staphylococcus vitulus RS34 as the starter culture (P200S34), separately and together, ripened for 90 days, and compared to a control batch. Among the ripening time points (20, 35, 65, 90 days) studied, batches inoculated with EPg222 had higher nitrogen compound concentrations at 63 days of ripening. ACE-inhibitory and antioxidant activities were also highest in both batches with EPg222 at 63 days of ripening, and these activities were stable in most cases after in vitro simulated gastrointestinal digestion. These activities were correlated with the most relevant compounds detected by HLPC-ESI-MS. The principal components analysis (PCA) linked the P200S34 + EPg222 batch with the major compounds identified. The antioxidant activity was higher at 63 days of ripening, especially in highly proteolytic batches, such as P200S34 + EPg222. The ACE-inhibitory activity was not associated with any of the major compounds. The use of the enzyme EPg222 in association with the starter culture P200S34 in the preparation of dry-cured meat products could be of great importance due to their demonstrated ability to produce compounds with high biological activity, such as ACE-inhibitory and antioxidant activity.